Negotiating Intersecting Minority Identities: The Cultural Transitioning of Jewish Argentinean Immigrants - Sinacore, Ada L.; Khayutin, Sarah; Nasrullah, Shakib; Titus, Jennifer (Canadian Journal of Counselling and Psychotherapy, 2017)
This phenomenological qualitative study employed relational cultural theory and feminist social constructionist theory as epistemologies to examine the role of multiple intersecting identities in the cultural transitioning of Jewish Argentinean immigrants into a range of relational and social contexts. Results indicated that identity salience across different relational contexts was strongly influenced by the emergence of the immigrant identity and the resulting interpersonal challenges. Implications for future research and counselling are discussed.